Leadership Challenges and Coping Strategies of Community Health Nurses (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The leadership abilities of a nurse is a key part of effective nursing care. Nurses in any field of practice, including community health nursing, must demonstrate leadership skills by providing, facilitating and promoting the best possible care for their patient. Thus, it is imperative that nurses must develop leadership abilities in order to effectively perform their roles and functions as primary patient care providers. This study determined the leadership challenges and coping strategies of community health nurses in selected municipalities. Descriptive correlational research was employed. A researcher modified questionnaire was used to obtain the profile of the respondents as well as their leadership challenges and coping strategies. Forty (40) community health nurses were included as research respondents. Majority of the respondents were ages of 18 to 39 years old, female, registered or licensed nurses with more than 3-years length of service. Overall, the respondents are less challenged in all four leadership domains as to challenges to self, challenges to communication, challenges with supervisor and organizational challenges; but presented as moderately challenged in some of the specific indicators for each domain. They also moderately utilized the different coping strategies, with high utilization on planful problem-solving as a coping strategy in the performance of their leadership functions while confrontative coping is the least coping strategy used. In general, the profile of the respondents has significant relationship to their leadership challenges and coping strategies, however, gender and educational attainment showed no significant relationship to both. Leadership challenges have significant relationship to coping strategies. In conclusion, community health nurses are facing different leadership challenges in their leadership roles and responsibilities. The ability of the nurse leader to effectively cope with the challenges imposed by her leadership functions will greatly aid her in positively performing her tasks and influencing better performance of her team. It is recommended that further studies on leadership profile, leadership styles and leadership training needs be implement based on the study’s findings.